Thermal Variation during Osteotomy with Different Dental Implant Drills: A Standardized Study in Bovine Ribs - Hochscheidt, Celso João; Shimizu, Roberto Hideo [UNESP]; Andrighetto, Augusto Ricardo; Moura, Luís Mauro; Golin, Alexsander Luiz; Hochscheidt, Regina Célia (Wolters Kluwer, 2017)
Introduction: This study evaluated thermal variation (heat generation) by dental drills of similar geometries, made from different materials, during performance of 450 standardized osteotomies in bovine ribs to simulate implant site preparations. Materials and Methods: Each of the 3 groups-steel with a diamond-like carbon coating (SG), experimentally surface-treated steel (EG), and aluminum-toughened zirconium ceramic (ZG)-included 3 drills, distributed across 6 subgroups. An implant motor provided torque, rotation, and irrigation for 50% of subgroups. Results: In preparations drilled to 5 mm under irrigation, the number of osteotomies, material, and diameter did not influence thermal variation (ΔT); when drilling to 13 mm, the greatest ΔT occurred in EG (2.8°C). When drilling to 5 mm without irrigation, drill material influenced mean temperature; when drilling to 13 mm without irrigation, the greatest ΔT (5.5°C) occurred in EG. The highest temperature was observed in SG (79.6°C). Conclusion: After 50 uses, the greatest ΔT occurred in EG and the 3.0-mm drill exhibited the highest mean and peak temperatures. Temperatures were influenced by irrigation, number of uses, depth, drill diameter, geometry, and material; however, mean values were within physiological limits.
Keywords: ceramics; damage reduction; osteotomy; stainless steel